Bidirectional urban flows in rapidly urbanizing metropolitan areas and their macro and micro impacts on urban growth: A case study of the Yangtze River middle reaches megalopolis, China. (March 2019) - Xia, Chang; Zhang, Anqi; Wang, Haijun; Zhang, Boen; Zhang, Yan
Abstract: Bidirectional urban flows of materials, technologies and information are becoming more frequent, and cities are closely connected socially, economically and technologically. Thus, an open, mobile and polycentric urban network has gradually formed. However, most of the recent studies on urban landscape dynamics regarded each city as a single entity and ignored intercity relatedness. In this study, we took as an example the Yangtze River middle reaches megalopolis (YRMRM), which is one of the rapidly urbanizing metropolitan areas in China. We pose two research questions: (1) Do intercity factors impact the expansion of urban land at a macro level? (2) Do intercity factors impact the spatial patterns of urban growth at a micro level? We used geospatial big data to measure urban relatedness and spatial interaction among city groups from a macro perspective. Then, a spatially explicit approach based on a data field model was adopted to quantify the micro urban spatial interaction inside each city. The pattern of spatial interaction and its impacts on urban growth were also analysed. The results showed that the three city sub-groups developed well, with Wuhan, Nanchang and Changsha being the dominant cores. However, the macro intercity relatedness in the YRMRM has not broken the shackles of the geographical boundaries of the provinces. A highly connected polycentric urban network system has not been formed to date. Our empirical results indicated that intercity factors were the main drivers of both macro and micro urban growth dynamics in the YRMRM from 2005 to 2015. This finding suggests that population and information flows had strong effects on the promotion of urbanization in the YRMRM during this period. Thus, we argued that urban bidirectional flows should be a vital consideration in future urban spatial planning and regional development strategies.